Upaya Penguatan Tata Kelola Desa Adat Yang Efektif Dan Berkelanjutan Untuk Menjaga Keajegan Alam, Manusia, Dan Budaya Bali - I Made Endra Lesmana Putra; Ni Made Wisni Arie Pramuki; Putu Atim Purwaningrat; Gde Indra Surya Diputra; Komang Indra Apsaridewi; Made Gede Arthadana (Jurnal Pengabdian Masyarakat Akademisi, 2026)
This community service activity (Pengabdian kepada Masyarakat, PkM) was carried out as an effort to strengthen the governance of Desa Adat (Traditional Villages) in Bali Province, which possess a central role in maintaining tradition, custom, and the sustainability of Balinese Nature, People, and Culture. The background of this activity is the urgent need to enhance the competency of the Human Resources (SDM) of the Bendesa Adat to ensure development planning is effective, transparent, and based on good governance principles. This urgency is emphasized in the context of implementing new policies, namely Regional Regulation (Perda) Number 4 of 2019 and Law (UU) Number 15 of 2023. This socialization program was realized through the Widya Sancaya #4 Webinar, held online on July 30, 2025. It was organized by the Center for Traditional Village Studies (Pusat Kajian Desa Adat) at Universitas Hindu Indonesia, targeting all Bendesa Adat in Bali Province. The method utilized involved comprehensive presentations by expert speakers regarding the issues surrounding the relationship between the Traditional Village Council (Majelis Desa Adat, MDA) and the Desa Adat as autonomous entities, as well as governance post-new regulations. The activity was successfully conducted smoothly and met its targets, achieving its goal of providing in-depth information, knowledge, and understanding to the participants. The positive response from the Bendesa Adat indicated appreciation and hope that similar programs could be carried out continuously. The expected outcome is the formulation of strategic steps that can strengthen the implementation of regulations/policies, for the purpose of maintaining Bali's sustainability (Ajeg).